DIOPHANTINE EQUATIONS AND THEIR APPLICATION - Islamov, Khurram; Mamatmurotov, Rufatbek Sherzodovich; Raimkulov, Sherali Urazdavlatovich (SCIENCE and SOCIETY, 2026)
This article discusses the problems of linear Diophantine equations and the conditions for the existence of a unique solution, as well as their practical applications. The article highlights the areas of application of Diophantine equations in modern science and technology.